United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2003 (A & B) - United Nations (United Nations, 2008)
The Yearbook covers the Commission’s report on its work as well as related documents, studies, reports and notes. It also looks at specific subjects such as assignment in receivables financing; electronic commerce; and privately financed infrastructure projects. In addition, the Yearbook provides information on related actions undertaken by the United Nations Conference on Trade and Development (UNCTAD) and the General Assembly.